Iron(III)-Catalysed Povarov Cyclisation for the Synthesis of Fused Dibenzo[b,f][1,7]naphthyridine Embedded Arylpyrrolo Scaffolds - Sahoo, Raj Kamal; Rana, Gopal; Kar, Abhishek; Ghosh, Sourav; Jana, Umasish (Synthesis, 2024)
An FeCl3-catalyzed Povarov reaction for the efficient synthesis of dibenzo[b,f][1,7]naphthyridines utilizing 1-(2-alkynylaryl)-2-pyrrolecarbaldehydes and arylamines in excellent yields is demonstrated. The essential features of the present strategy are easy preparation of substrates, broad substrate scope, mild reaction conditions, and high atom economy and yields, in the presence of environmentally friendly iron catalysis.
Keywords: arylpyrrolecarbaldehydes; phosphorus oxychloride; arylamines; 1,7-naphthyridines; ferric chloride